Shorter treatment for multidrug-resistant tuberculosis: the good, the bad and the ugly. Issue 6 (6th October 2016) - van Altena, Richard; Akkerman, Onno W.; Alffenaar, Jan-Willem C.; Kerstjens, Huib A.M.; Magis-Escurra, Cecile; Boeree, Martin J.; van Soolingen, Dick; de Lange, Wiel C.M.; Bolhuis, Mathieu S.; Hoefsloot, Wouter; de Vries, Gerard; van der Werf, Tjip S.
We welcome the initiative by the Guideline Development Group (GDG) members to issue the 2016 update of World Health Organization (WHO) treatment guidelines for drug-resistant tuberculosis (TB) [1]. With one in two patients currently failing on treatment for multidrug-resistant (MDR)-TB, primarily as a result of the difficulties presented by cumulative drug toxicity, logistics, costs and subsequent poor adherence to therapy [2], a shorter regimen for selected patients would be a tremendous asset, even though the GDG argues that the recommendation is conditional, and the scientific evidence for the recommendation is low. Since the first reports on the efficacy of a regimen of only 9 months for MDR-TB [3, 4], two more studies have been published to support the concept of shorter regimens [5, 6] while the STREAM (Evaluation of a Standard Treatment Regimen of Anti-tuberculosis Drugs for Patients with MDR-TB) study is still enrolling [7]. However, shortening therapy would only apply for selected patients without prior use of or proven resistance to fluoroquinolones (group A) or second-line injectable agents (group B). At least five active drugs should be available for the intensive phase (4–6 months). Further exclusions are extrapulmonary TB, additional resistance to pyrazinamide (PZA) and pregnancy. Clofazimine [8] and linezolid [9] were regrouped as core agents in group C with ethionamide or prothionamide, while para-aminosalicylic acid was deferred to group D. Updated WHO guidelines advise 9–12 months of MDR-TB treatment; this was suitable for 85 out of 172 Dutch patients http://ow.ly/OClA303L181